Joint - studio as an alternative method to enhance student's learning experience - Utaberta, Nangkula; Ismail, Zamri; Wong, Kail Li; Sim, Chuan; Nica Lisandria,; Auziny Rahmah, (Universiti Putra Malaysia Press, 2014)
The core of an architectural education curriculum is based on the design studio model which focuses on learning by doing and the processes and procedures of problem solving are transmitted trough lectures and critique sessions. This paper tries to unfold issues and problems behind the Joint-Studio Program (JSP), which is one of the methods to enhance the pedagogical process of the 3rd year architectural studio at the Architecture Department, Universiti Putra Malaysia (UPM). The discussion will consist of four parts which are the general understanding of design studio in architecture, JSP as part of learning process in studio, critical analysis of JSP at 3rd year between UPM and Islamic State University of Malang (UIN), Indonesia and some recommendations for future JSP. It is expected that this paper can start more critical discussions on the pedagogical output of JSP as part of student's learning experience in the architecture design studio.